An Eight Year Experience of Autologous Oocyte Vitrification for Infertile Patients Owing to Unavailability of Sperm on Oocyte Retrieval Day - Fu, Xiao; Liu, Xiaojie; Li, Jing; Zhang, Meng; Jiang, Jingjing; Chen, Qianqian; Li, Mei; Gao, Shanshan; Ma, Jinlong (Frontiers in Medicine, 2021)
The objective of this study was to provides a descriptive analysis of the clinical outcomes achieved in oocyte vitrification in cases of unavailable sperm on oocyte retrieval day, and to find predictors of oocyte survival.This retrospective cohort study used data from a university-affiliated reproductive medicine center. There were 321 cycles carried part or all oocytes vitrification due to unavailability of sperm from March 2009 to October 2017. A descriptive analysis of the clinical outcomes including both fresh embryo transfers and cryopreserved embryos transfers was provided. The ability of an individual parameter to forecast oocyte survival per thawing cycle was assessed by a binary logistic regression analysis. The cumulative probability of live birth (CPLB) was estimated by using the K-M method according to the total number of oocytes consumed in consecutive procedures. The average survival rate was 83.13% (95% CI 81.81-86.35%). High-quality embryo rate decreased significantly (33.33% vs. 53.75%, P<0.0001) comparing to fresh control oocytes. The live birth rate per warmed-oocyte was 4.3%. Reasons for lack of sperm availability on oocyte retrieval day and serum cholesterol level were found to be associated with oocytes survival rate in present study. The Kaplan–Meier analysis showed no significantly different CPLB between patients ≤35 versus >35 years.Oocyte vitrification is proved to be an indispensable and effective alternative when lack of available sperm on oocyte retrieval day. Present study provided evidences that the oocytes from infertile population were more likely suffer to vitrification injury. Clinicians need to take this into account when giving suggestions to patients for similar situations. Further studies will be necessary to clarify the correlation between serum metabolism parameters and human oocyte survivability after vitrification.